Social music machine: crowdsourcing for composition & creativity - Chamberlain, Alan; De Roure, David; Willcox, Pip (2017)
This poster describes a compositional technique that used crowd-sourced midi clips in order to develop a piece of music, which was later performed. This work in progress highlighted some of the issues facing the designers of systems that enable the ‘crowd’ to compose.